Efektifitas Pelvic Rocking Exercise untuk Memajukan Persalinan Kala I: A Literature Review - Lilis Mamuroh; Sukmawati Sukmawati; Furkon Nurhakim (Universitas Malahayati Lampung, 2025)
ABSTRACT Childbirth is a process of expelling the products of conception (foetus and placenta) at term through the birth canal or with or without assistance. The problem that is often found during childbirth is prolonged labour, which is one of the causes of maternal and infant death. One of the efforts to deal with prolonged labour is doing exercises, namely pelvic rocking exercise. This research is to determine the effectiveness of pelvic rocking exercise on the length of time in the first stage of labour. This research uses a literature review system with PRISMA, literature search from the PubMed EBSCO, Science Direct, and CINAHL databases. With the keywords parture in women OR mother giving birth, pelvic rocking exercise, stage of labour OR labour stage Parturient women OR mothers giving birth and pelvic rocking exercise AND stage of labour OR labour stage. After searching and analysing, there were 6 articles that were deemed to meet the criteria, with 5 research locations in Indonesia and 1 from Egypt. Pelvic rocking exercise (PRE) is a form of exercise that can be beneficial for mothers who are about to give birth. This exercise can strengthen the abdominal and waist muscles, reduce pressure on the waist, reduce pressure on blood vessels in the uterine area, and reduce pressure on the mother's bladder. The pelvic rocking exercise intervention is effective in shortening the first stage of labour because this intervention stimulates contractions more effectively to open the cervix.: Keywords: Effectiveness, Pelvic Rocking Exercise, First Stage of Labour ABSTRAK Persalinan adalah suatu proses pengeluaran hasil konsepsi (janin dan plasenta) yang cukup bulan melalui jalan lahir atau menggunakan bantuan atau tanpa bantuan. Masalah yang sering ditemukan pada waktu persalianan adalah partus lama yang merupakan salah satu penyebab kematian ibu dan bayi. Salah satu upaya penanganan pada partus lama yaitu melakukan latihan yaitu Pelvic rocking exercise. Penelitian ini adalah untuk mengetahui efektifitas pelvic rocking exercise terhadap lama waktu persalinan kala I. Penelitian ini menggunakan sistem literature review dengan PRISMA,pencarian literature dari data base PubMed EBSCO, Science Direct, CINAHL. Dengan kata kunci Parturein women OR Mother giving birth, pelvic rocking exercise, sstage of labor OR Labor stage Parturient women OR Mother giving birth and pelvic rocking exercise AND stage of labor OR Labor stage. Setelah dilakukan pencarian dan analisis terdapat 6 artikel yang dinilai memenuhi krteria dengan lokasi penelitian 5 di Indonesia dan 1 dari Mesir. Pelvic rocking exercise (PRE) merupakan salah satu bentuk latihan yang dapat menguntungkan bagi ibu yang akan menghadapi persalinan latihan ini dapat memperkuat otot –otot perut dan pinggang mengurangi tekanan pada pinggang dan dapat mengurangi tekanan pembuluh darah di area uterus dan mengurangi tekanan pada kandung kemih ibu. Intervensi Pelvic Rocking Exercise efektif dalam mempersingkat persalinan Kala I karena intervensi ini merangsang kontraksi lebih efektif untuk pembukaan serviks Kata Kunci: Efektivitas, Pelvic Rocking Exercise, Persalinan Kala I